Analisis Molekuler dan Uji Ketahanan Tanaman Padi Transgenik yang mengandung Gen Kitinase Generasi ke tiga (T2) terhadap Rhizoctonia solani Kuhn dan Pyricularia oryzae Cav - E. S. Mulyaningsih; S. Indrayani; I.H. Slamet Loedin (Fakultas Biologi | Universitas Jenderal Soedirman, 2005)
Sheath blight and rice blast are two important diseases in rice caused respectively by fungi Rhizoctonia solani and Pyricularia oryzae resulting in considerable yield loss. A study on the segregation pattern of chiI gene among four progenies, i.e. lines 1,7,9 and 20, followed by bioassays of both pathogens was conducted. PCR analysis using specific primers for chiI gene in 30 plant samples from each line was employed to know the segregation pattern. The results showed that three of the four lines, i.e. 1, 7, and 9 performed Mendelian segregation of 3 : 1. Southern blot analysis further applied on line 1 revealed the presence of six copies of chiI gene. Bioassay of P. oryzae carried out at vegetative phase indicated that all lines were susceptible to blast, on the other hands, R. solani bioassay held at heading phase showed that they were all resistant to this fungi.